PENINGKATAN PEMBELAJARAN PEMECAHAN MASALAH SOAL CERITA MENGGUNAKAN STRATEGI POLYA DI SEKOLAH DASAR - umar, umar; MASNILADEVI, MASNILADEVI; INDRAWATI, TIN (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this research is to describe the improve learning problem solving about the story question of fractions by using Polya strategi at class IVA SD Negeri 23 Marapalam Kota Padang. Research subjects were teachers (practitioners) and 32 students. The type of this research is classroom action research. Based on the results of the study, that learning using Polya strategi can improve learning outcomes about the story of  fractions at class SD IVA Negeri 23 Marapalam Kota Padang, Namely (a) Observation of RPP 75% with kualifikasi enough (C) becomes 96.4% (SB) with kualifikasi very good. (b) Teacher aspect 77,7% with kualifikasi  good (B) becomes 94.5% with kualifikasi very good (SB). (c) Student aspect 75% with kualifikasi enough (B) becomes 94.5% with kualifikasi very good (SB). (d) Student learning outcomes 74,7 with kualifikasi enough (C) becomes 88.4 with kualifikasi very good (SB)